Lithium-aluminum-silicon glass ceramic and preparation method thereof

By regulating the composition and sintering process of lithium aluminum silicon glass ceramics, the problem of insufficient mechanical and thermal performance of optical fiber ferrule materials in high transmission rate and high bandwidth technologies is solved, and the preparation of high density and high crystallinity is achieved , suitable for high-precision fiber optic ferrules and reduces production costs.

CN119161105APending Publication Date: 2024-12-20YANGTZE OPTICAL FIBRE & CABLE CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411365487.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing fiber optic ferrule materials such as zirconium dioxide ceramics, glass, metals and plastics have problems such as high transmission rates and high bandwidth optical fiber communication technologies, such as high process, high cost, and mechanical and thermal performance that cannot meet the requirements.

Method used

Through the coordinated regulation of the composition design of lithium-aluminum silicon glass ceramics and the sintering crystallization process, specific oxide ratios and sintering temperature control are adopted to achieve the preparation of lithium-aluminum silicon glass ceramics with high density and high crystallinity, with low cost and Excellent mechanical properties.

Benefits of technology

It realizes crystallization and exhausts bubbles at lower temperatures, and obtains lithium-aluminum silicon glass ceramics with high density and high crystallinity. The thermal expansion coefficient is close to that of optical fibers and has high flexural strength. It is suitable for high-precision optical fiber core materials, reducing production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161105A_ABST
    Figure CN119161105A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-aluminum-silicon glass ceramic and a preparation method thereof. The lithium-aluminum-silicon glass ceramic is prepared from the following raw materials in percentage by mole: 58.0-70.0% of SiO2; the content of Al2O3 is 13.0%-16.4%; 8.3% to 16.5% of Li2O; 0.5% to 1.5% of Na2O; less than or equal to 10% of divalent metal oxide; 0.2% to 2.1% of ZrO2; 0.2% to 1.3% of TiO2; the divalent metal oxide is any one or any mixture of ZnO, MgO and CaO; according to the preparation method disclosed by the invention, the two processes of glass ceramic component design and sintering devitrification are cooperatively regulated and controlled, so that devitrification can be carried out at a relatively low temperature while bubbles are smoothly discharged, and the high-density and high-crystallinity lithium-aluminum-silicon glass ceramic is obtained; after the lithium-aluminum-silicon glass ceramic is sintered at 850 DEG C for 2-5 hours, the density can reach at least 80% of the maximum sintering density, the crystallinity reaches 85% or above, the thermal expansion coefficient is-0.5 to 3.5 * 10 <-6 > K <-1 >, the breaking strength is greater than 100 MPa, and the lithium-aluminum-silicon glass ceramic has excellent machinability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic materials, and in particular relates to a lithium aluminum silicon glass ceramic for an optical fiber insert and a preparation method thereof. Background Art

[0002] In the field of optical fiber communication technology, optical fiber active connection technology has been developed along with the development of optical fiber communication technology. At present, it has developed into a series of optical fiber connector products with a wide variety of types, complete categories and diverse structures, and has become one of the most widely used basic optical passive components in the field of optical fiber application. Optical fiber connectors can be used to transmit optical signals. At present, optical fiber communication technology is developing in the direction of high transmission rate and high bandwidth, and higher requirements are also put forward for the performance of optical fiber connectors.

[0003] The core component of the optical fiber connector is the optical fiber ferrule. Currently, the most commonly used optical fiber connector materials include zirconium dioxide ceramics, glass, metal and plastic. Metal optical fiber connectors are difficult to process, have poor corrosion resistance and wear resistance, and are difficult to mass produce; glass has poor impact resistance; plastics are not precise enough and have poor strength; zirconium dioxide ceramics have complex processes and high sintering costs.

[0004] Glass ceramics are an important structural and functional glass material with high performance, low cost and simple processing. The evenly distributed grains in glass ceramics enable the material to combine the advantages of both glass and ceramics, with high mechanical strength, low cost and a suitable thermal expansion coefficient.

[0005] At present, there are two main ways to prepare glass ceramics: overall crystallization and sintering. Glass ceramics prepared by the overall crystallization method usually have a higher density and do not contain bubbles, but the crystallinity is low. Excessive glass phase makes the mechanical and thermal properties of the overall crystallization glass ceramics unable to meet the requirements of high-precision fiber optic ferrules. Sintered microcrystalline glass usually has a high crystallinity with the rich interface of the powder as the nucleation site, but sintering will introduce pores in the microcrystalline glass. For glass ceramic systems with fast crystallization, crystals are prone to precipitate in large quantities before sintering, hindering sintering and requiring higher temperatures to discharge the pores. For crystals that are difficult to crystallize, crystals will precipitate after sintering, and the volume shrinkage of the crystals will introduce pores. Summary of the invention

[0006] In view of the above problems, the present invention provides a high-density and high-crystallinity lithium-aluminum-silicon glass-ceramic suitable for optical fiber ferrule and a preparation method thereof. By designing the glass-ceramic composition and coordinating the two processes of sintering and crystallization, bubbles can be discharged smoothly at a lower temperature to obtain a high-density and high-crystallinity lithium-aluminum-silicon glass-ceramic. The density of the lithium-aluminum-silicon glass-ceramic after sintering at 850°C for 2 to 5 hours can reach at least 80% of the maximum sintering density, the crystallinity reaches more than 85%, and the thermal expansion coefficient is between -0.5 and 3.5×10 -6 K -1 It has a thermal expansion coefficient similar to that of optical fiber, a flexural strength greater than 100MPa and excellent processability.

[0007] In order to achieve the above purpose, the technical solutions adopted are as follows:

[0008] A lithium aluminum silicon glass ceramic, the raw material composition of which, calculated by molar percentage of oxides, comprises:

[0009] SiO2 58.0%~70.0%;

[0010] Al2O3 13.0%~16.4%;

[0011] Li2O 8.3%~16.5%;

[0012] Na2O 0.5%~1.5%;

[0013] Divalent metal oxides ≤ 10%;

[0014] ZrO2 0.2%~2.1%;

[0015] TiO2 0.2%~1.3%;

[0016] The divalent metal oxide is any one of ZnO, MgO and CaO or any mixture thereof.

[0017] According to the above scheme, in the optimized scheme, the divalent metal oxides are ZnO, MgO and CaO; the amount of ZnO is 2.3%, the amount of MgO is 4.0%, and the amount of CaO is 3.0%.

[0018] According to the above scheme, in the optimized scheme, the divalent metal oxides are ZnO and MgO; the amount of ZnO is 2.3% and the amount of MgO is 4.0%.

[0019] According to the above scheme, in the optimized scheme, the divalent metal oxides are ZnO and CaO; the amount of ZnO is 2.3%, and the amount of CaO is 3.0%.

[0020] The preparation method of the lithium aluminum silicon glass ceramics comprises the following steps:

[0021] (1) weighing glass raw materials according to the molar percentage of the oxides, melting them at 1600° C. to 1750° C. for 2 to 3 hours to obtain a uniform glass melt, quenching the melt to obtain a matrix glass, and grinding to obtain a basic glass powder;

[0022] (2) mixing the basic glass powder and a binder, and die-casting the mixture in a mold to obtain a green body;

[0023] (3) The obtained green embryo is sintered in a furnace at 850-1200°C for 1-5 hours;

[0024] (4) After cutting, grinding and polishing, lithium aluminum silicon glass ceramics are obtained.

[0025] According to the above scheme, the particle size of the basic glass powder in step 1 is 0.4μm-3μm

[0026] According to the above scheme, the binder in step 2 is any one of polyvinyl butyral, acrylic resin, methyl cellulose, ethyl cellulose, nitrocellulose ester, polyurethane resin, polyester resin, and pinene alcohol, or a mixture thereof; the mass ratio of the base glass powder to the binder is 1:(0.02-0.075).

[0027] According to the above scheme, the die-casting pressure in step 2 is 1.0-4.0 MPa, and the holding time is greater than 120 s.

[0028] According to the above scheme, the sintering atmosphere in step 3 is air.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] In the present invention, Na2O is used at 0.5% to 1.5%, and its function is to increase the types of alkali metals in the glass ceramic system, have a certain inhibitory effect on the precipitation of target crystals, and slow down the crystallization rate. The divalent metal oxide is any one of ZnO, MgO, and CaO or any mixture thereof, and the amount is ≤10%; its function is to slow down the crystallization rate, and at the same time, it can be incorporated into the lattice of spodumene crystals to regulate the thermal expansion coefficient of the glass ceramic as a whole. ZrO2 is used at 0.2% to 2.1%, and TiO2 is used at 0.2% to 1.3%, and their function is to provide some nucleation sites during the sintering process, reduce the temperature required for crystallization, and match the sintering temperature range.

[0031] Compared with the current fiber optic core materials such as zirconium oxide, the high-density and high-crystallinity lithium-aluminum-silicon glass ceramics provided by the present invention have a very low sintering temperature while maintaining a relatively high mechanical strength, and can produce significant benefits in controlling production costs. By designing the glass ceramic composition and sintering and crystallizing, regulating the softening point temperature and crystallization temperature of spodumene crystals, reducing the crystal growth rate in the glass so that the sintering and crystallization processes are coordinated and matched, crystallizing at a relatively low temperature and smoothly discharging bubbles, a high-density and high-crystallinity lithium-aluminum-silicon glass ceramic is obtained.

[0032] The main crystal phase of the lithium aluminum silicon glass ceramic obtained by the present invention is β-spodumene, which has a low thermal expansion coefficient. By controlling the pore content and divalent metal ion doping during sintering, the thermal expansion coefficient of the microcrystalline glass of the present invention is -0.5 to 3.5×10 -6 K -1 , can be used as optical fiber ferrule material for a variety of optical fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 : Sintering curves of Examples 1-4.

[0034] Figure 2 : Density of glass ceramics of Example 1 at different sintering temperatures. DETAILED DESCRIPTION

[0035] The following examples further illustrate the technical solution of the present invention, but are not intended to limit the scope of protection of the present invention.

[0036] A specific embodiment provides a lithium aluminum silicon glass ceramic, whose raw material composition, calculated by molar percentage of oxides, includes: SiO2 58.0% to 70.0%; Al2O3 13.0% to 16.4%; Li2O 8.3% to 16.5%; Na2O 0.5% to 1.5%; divalent metal oxide ≤ 10%; ZrO2 0.2% to 2.1%; TiO2 0.2% to 1.3%; the divalent metal oxide is any one of ZnO, MgO, CaO or any mixture thereof.

[0037] A specific embodiment provides a method for preparing lithium aluminum silicon glass ceramics, comprising the following steps:

[0038] Preparation of basic glass powder: Weigh the glass batch materials according to the designed ratio, melt them at 1600℃~1750℃ for 2~3h to obtain a uniform glass melt, quench the melt with water to obtain matrix glass, and grind to obtain matrix glass powder with a powder particle size of 0.4μm-3μm.

[0039] Preparation of green embryo: weigh basic glass powder and adhesive respectively and mix them; wherein the adhesive is selected from any one of polyvinyl butyral, acrylic resin, methyl cellulose, ethyl cellulose, nitrocellulose ester, polyurethane resin, polyester resin, and pinene alcohol or a mixture thereof; the mass ratio of the basic glass powder to the adhesive is 1:(0.02-0.075); the mixture is die-casted in a mold at a pressure of 1.0-4.0 MPa and the pressure holding time is greater than 120 seconds.

[0040] Sintering crystallization: After forming, the green embryo is sintered in a high temperature furnace at a sintering temperature of 850-1200°C and a sintering time of 1-5 hours.

[0041] Sample processing: cutting, grinding and polishing the glass ceramics formed in the above steps to prepare glass ceramics that meet the shape requirements.

[0042] In a specific embodiment, the raw material containing SiO2 is selected from common raw materials for glass melting such as high-purity quartz sand and quartz powder. The raw material containing Al2O3 is selected from common raw materials for glass melting such as high-purity corundum sand and corundum powder. The raw material containing Li2O is selected from common raw materials for glass melting such as lithium carbonate, high-purity ore containing lithium, spodumene and petalite. The raw material containing Na2O is selected from common raw materials for glass melting containing sodium such as soda ash. The raw material containing ZrO2 is selected from analytically pure zirconium oxide. The raw material containing TiO2 is selected from analytically pure titanium dioxide. The raw material containing ZnO is selected from common raw materials for glass melting containing zinc oxide. The raw material containing MgO is selected from common raw materials for glass melting containing magnesium such as magnesite. The raw material containing CaO is selected from common raw materials for glass melting containing calcium such as limestone.

[0043] The raw material compositions of the examples are shown in Table 1 in terms of molar percentage of oxides. The key process parameters of the preparation process of each example are shown in Table 2. The performance characteristics of the products obtained in each example are shown in Table 3.

[0044] Table 1

[0045]

[0046] Table 2

[0047]

[0048] Table 3

[0049]

[0050] The DIL 402E ultra-high temperature thermal expansion instrument from NETZSCH of Germany and the Instron 5967 dual-column tabletop material testing machine from Instron of the United States were used to test the surface thermal expansion and bending strength of the samples. The dielectric constant was tested using the Agilent E4990A produced by Keysight Technologies (fixed test frequency 1 MHz).

[0051] Comprehensive comparison data show that the lithium aluminum silicon glass ceramics in Examples 1-4 prepared by the technical solution of the present invention have a thermal expansion of 1.0 to 2.0×10 -6 K -1 , the bending strength is above 110MPa, and the crystallinity is above 85%. It can be seen that the lithium aluminum silicate glass ceramic of the present invention has both high crystallinity and high density, and its main crystal phase is β-spodumene, which is a crystal with high mechanical strength, low expansion coefficient and low dielectric loss. The large amount of precipitation of this crystal makes the lithium aluminum silicate glass ceramic also have excellent performance, and is suitable for advanced optical fiber core materials.

[0052] The sintering curves of Examples 1-4 and the density of the glass ceramic of Example 1 at different sintering temperatures are shown in the attached Figure 1 and attached Figure 2 As shown. It can be seen that the glass ceramics of Example 4 exhibited very significant sintering shrinkage behavior at around 800°C, and the density after sintering at 800°C was already relatively high, reaching about 95% of the density sintered at 1100°C. Compared with ceramic powders such as zirconium oxide and aluminum oxide used to manufacture optical fiber ferrules with a sintering temperature exceeding 1000°C, this solution can significantly reduce production costs and has obvious advantages.

[0053] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium aluminum silicon glass ceramic, characterized in that The raw material composition is calculated as follows based on the molar percentage of oxides: SiO2 58.0%~70.0%; Al2O3 13.0%~16.4%; Li2O 8.3%~16.5%; Na2O 0.5%~1.5%; Divalent metal oxides ≤ 10%; ZrO2 0.2%~2.1%; TiO2 0.2%~1.3%; The divalent metal oxide is any one of ZnO, MgO and CaO or any mixture thereof.

2. The lithium aluminum silicon glass ceramic according to claim 1, characterized in that The divalent metal oxides are ZnO, MgO and CaO; the amount of ZnO is 2.3%, the amount of MgO is 4.0% and the amount of CaO is 3.0%.

3. The lithium aluminum silicon glass ceramic according to claim 1, characterized in that The divalent metal oxides are ZnO and MgO; the amount of ZnO is 2.3% and the amount of MgO is 4.0%.

4. The lithium aluminum silicon glass ceramic according to claim 1, characterized in that The divalent metal oxides are ZnO and CaO; the amount of ZnO is 2.3% and the amount of CaO is 3.0%.

5. The method for preparing the lithium aluminum silicon glass ceramic according to claim 1, characterized in that The following steps are involved: (1) weighing glass raw materials according to the molar percentage of the oxides, melting them at 1600° C. to 1750° C. for 2 to 3 hours to obtain a uniform glass melt, quenching the melt to obtain a matrix glass, and grinding to obtain a basic glass powder; (2) mixing the basic glass powder and a binder, and die-casting the mixture in a mold to obtain a green body; (3) The obtained green embryo is sintered in a furnace at 850-1200°C for 1-5 hours; (4) After post-processing, lithium aluminum silicon glass ceramics are obtained.

6. The method for preparing lithium aluminum silicon glass ceramics for optical fiber ferrule according to claim 5, characterized in that In step 1, the particle size of the basic glass powder is 0.4 μm-3 μm.

7. The method for preparing lithium aluminum silicon glass ceramics as claimed in claim 5, characterized in that The binder in step 2 is any one of polyvinyl butyral, acrylic resin, methyl cellulose, ethyl cellulose, nitrocellulose ester, polyurethane resin, polyester resin, and pinene alcohol, or a mixture thereof; the mass ratio of the base glass powder to the binder is 1:(0.02-0.075).

8. The method for preparing lithium aluminum silicon glass ceramics as claimed in claim 5, characterized in that In step 2, the die-casting pressure is 1.0-4.0 MPa, and the holding time is greater than 120 s.

9. The method for preparing lithium aluminum silicon glass ceramics as claimed in claim 5, characterized in that The sintering atmosphere in step 3 is air.

10. The method for preparing lithium aluminum silicon glass ceramics according to claim 5, characterized in that The post-processing process in step 4 includes cutting, grinding and polishing.

Citation Information

Cited By

  • Glass ceramic composite optical fiber as well as preparation method and application thereof

    CN121779005A